Educational Financing Management on the Quality of Vocational High Schools - Meta Rostiani; Rajaminsah; Andri Feriyansyah; Cecep Badrudduja (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research aims to determine the Management of Educational Financing on the Quality of Vocational High Schools. This research was conducted against the background of the importance of financing management in vocational high schools on school quality. The general purpose of this study is to describe the management of education financing on the quality of vocational secondary schools. The specific objectives of this study are to describe: education financing management planning, organizing education financing management, implementing education financing management, and evaluating education financing management and accountability. This research method is descriptive qualitative research. This research uses a library research approach. The results of this research indicate that vocational school principals are able to carry out optimal education financing management in terms of planning, organizing, implementing and evaluating/supervising educational financing. To achieve good school quality, education costs can be managed optimally and optimally.